Factors influence studying in rural area and student's academic performance / Siti Mahsari Sataria - Sataria, Siti Mahsari (2013)
The purpose of this study was to study factors influence studying at Kolej Yayasan Felda Kampus Mempaga in rural area and students' academic performance. The research was done in Kolej Yayasan Felda Kampus Mempaga. Studies are made to understand, maintain, and control the results that may be acquired later. Study results will be used to identify the factors influence studying at rural area and student's academic performance. The researcher has selected 130 respondents from Kolej Yayasan Felda Kampus Mempaga. The respondents were the students from Kolej Yayasan Felda Kampus Mempaga from five courses which are Pramusaji Program, Pastry Program, Culinary Program, Front Office Assistant Program and Housekeeping Program. Survey instrument was conducted by using questionnaires and the researcher has used Likert Scale to identify the level of agreement of the respondents. The importance of this research was to identify the factors that influence studying at rural area and students' academic performance.